Distribución potencial de Podocarpus oleifolius D. Don: variables que explican su distribución espacial en un contexto de cambio climático, en la región sur del Ecuador - Quispe Castillo, Juan Pablo (2023)
Global climate change is composed of several meteorological phenomena that influence the functioning of ecosystems, in Ecuador, potential impacts are expected on high mountain and Amazonian ecosystems in which Podocarpus oleifolius D. Don is found. This research work has the following objectives: To analyze the bioclimatic and topographic variables that explain the potential distribution of Podocarpus oleifolius D. Don. in a context of climate change and modeling the current and future potential distribution of Podocarpus oleifolius D. Don, under climate change scenarios, for RCP 4.5 and 6.0 climate scenarios. The presence records were obtained from the Biological Information Service database worldwide, the environmental variables from CHELSA and CCAFS, the elevation from WorldClim and processed in ArcGIS. The models were valid through the ROC and True Skill Statistics considering a threshold 0,8. According to the results, the variables with the greatest contribution were isothermality, maximum temperature of the warmest month and annual mean temperature range. The current potential distribution of the species covers 3 228.52 km2, the scenario of greatest persistence is RCP 4.5-year 2080 with an area of 455.50 km2, the greatest displacement would occur in 2030 scenario RCP 6.0 with a gain of 744.46 km2 and the period with the greatest loss would be in 2080, the RCP 6.0 scenario of 2,862.57 km2. Podocarpus oleifolius D. Don has a wide distribution area, however, in the future a reduction of its distribution area is projected. Bioclimatic variables Isothermality Maximum temperature of the warmest month and the Annual Temperature Range determine its future distribution. Persistence represents climatically stable areas, where the species would remain, which is why they should be established as priority conservation areas. Keywords: Podocarpus, current distribution, future distribution, bioclimatic variables.